Trends and changes in the system of higher education in the United States for African-Americans and Hispanics - Nattie Golubov (Universidad Autónoma de Baja California, 2008)
Using a wide variety of statistical sources, particularly those created by government agencies in the United States of America (USA), this article offers a descriptive overview of the insertion of ethnic and racial minorities in the USA higher education system. This process illustrates more profound and general changes within USA society, which have a specific though not exclusive origin in the social transformations that began in the 1960's and were consolidated in the 1970's. These changes gave rise to a new polítical, social and cultural space for African-Americans, who waged a powerful battle to gain political and civil rights, which were then extended to the Hispanic population.